Pro WPF and Silverlight MVVM effective application development with Model-View-ViewModel - Hall, Gary McLean (Apress, 2010)
WPF and Silverlight are unlike any other user interface (UI) technologies. They have been built to a new paradigm that--if harnessed correctly--can yield unprecedented power and performance. This book shows you how to control that power to produce clean, testable, maintainable code. It is now recognized that any non-trivial WPF or Silverlight application needs be designed around the Model-View-ViewModel (MVVM) design pattern in order to unlock the technology's full data-binding potential.¡ However, the knowledge of how to do this is missing from a large part of the development community--even amongst those who work with WPF and Silverlight on a daily basis. Too often there is a reliance on programmatic interaction between controls and not enough trust in the technologies' data-binding capabilities. This leads to a clouding of design values and an inevitable loss of performance, scalability, and maintainability throughout the application. Pro WPF and Silverlight MVVM will show you how to arrange your application so that it can grow as much as required in any direction without danger of collapse.
Keywords: Silverlight (Electronic resource); User interfaces (Computer systems); Application software -- Development; Interfaces utilisateurs (Informatique); Logiciels d'application; Développement; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Informatique; Application software; Development